Youth Economic Empowerment Through Agribusiness In Kenya (Vijabiz) - Synthesis of Activities and Outcomes - Lohento, Ken (Technical Centre for Agricultural and Rural Cooperation, 2021)
Ustadi and CTA have jointly implemented the project “Youth economic empowerment through agribusiness in Kenya (VijaBiz)” in the Nakuru and Kilifi counties in Kenya. The project aimed to create sustainable employment for rural youth through active engagement in agribusiness for wealth creation and poverty reduction. More specifically, VijaBiz built entrepreneurship capacity for 163 youth agribusiness groups in cereals, dairy and fishery value chains in the Kilifi and Nakuru counties.